2017
DOI: 10.4012/dmj.2017-156
|View full text |Cite
|
Sign up to set email alerts
|

Non-biodegradable polymer particles for drug delivery: A new technology for “bio-active” restorative materials

Abstract: To develop dental restorative materials with "bio-active" functions, addition of the capability to release active agents is an effective approach. However, such functionality needs to be attained without compromising the basic properties of the restorative materials. We have developed novel non-biodegradable polymer particles for drug delivery, aimed for application in dental resins. The particles are made using 2-hydroxyethyl methacrylate (HEMA) and a cross-linking monomer trimethylolpropane trimethacrylate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Previous studies found it more effective than individual components. Other antibacterial agents like triclosan and cationic agents were also loaded [103]. What's more, to reduce the inflammatory response of pulp caused by deep dental caries, anti-inflammatory agents such as indomethacin have also been combined in the dental resin [104].…”
Section: Dds For Secondary Cariesmentioning
confidence: 99%
“…Previous studies found it more effective than individual components. Other antibacterial agents like triclosan and cationic agents were also loaded [103]. What's more, to reduce the inflammatory response of pulp caused by deep dental caries, anti-inflammatory agents such as indomethacin have also been combined in the dental resin [104].…”
Section: Dds For Secondary Cariesmentioning
confidence: 99%
“…Another approach to providing restorative materials with long-lasting antimicrobial effects is to apply non-biodegradable polymer particles as a reservoir of antimicrobials 2) . Imazato et al developed non-biodegradable polymer particles made of hydrophilic monomer 2-hydroxyethyl methacrylate (HEMA) and a cross-linking monomer trimethylolpropane trimethacrylate (TMPT) 2) ( Fig.…”
Section: Polymer Particles As a Reservoir Of Antimicrobialsmentioning
confidence: 99%
“…The basic mechanical, physical, esthetic, and bonding properties of dental restorative/coating materials have greatly improved with technological developments, and the current materials on the market show excellent clinical performance. Therefore, the target of their advancement is shifting towards bio-active functionality to prevent primary/secondary diseases or promote tissue regeneration 1,2) . Several properties are considered to be useful bio-active functions for dental materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations